Cotoneaster microphylla Wall. - a Suitable Species for Soil Conservation in Temperate Regions of Himalayas - Singh, R. P.; Prasad, Bhagwati; Bahar, Nawa (Indian Forester, 1992)
Cotoneaster microphylla Wall, seed has seed coat dormancy and concentrated sulphuric acid treatments proved effective in hastening germination. Roots of a single plant can bind soil upto 1.88 m2 with the strong lateral and fibrous roots The taper rate of lateral roots varies from 0.10 to 0.16 which itself is an indication of strong roots. Intricately branched aerial portion of this species spreads on an average over 2.26 m2 land surface and helps in checking splash erosion.